(untitled) (Texas Journal of Medical Science, 2022)
In the practice of the dental surgeon, odontogenic cysts make up 78–96% of the total number of cysts and 7–12% of the total number of diseases of the jaws. These figures indicate the relevance of the problem of treating this pathology. The priority tasks of surgical treatment of patients with odontogenic cystamias are the restoration of bone structure and the preservation of the function of the teeth. The main method of surgical treatment remains cystectomy with resection of the root apex. The disadvantages of cystectomy include the reduction of the function of the teeth in the area of the cyst, reinfection and residual bone cavities, which reduce the strength of the bone. Disruption of the integrity of the bone in the surgical area is often associated with prolonged healing, the outcome of which is incomplete or incomplete restoration of bone tissue